Zur Frage des Bedeutungswechsels im Deutschen und Georgischen - Eliso Koridze (Reviews of Modern Science, 2026)
Investigating the meaning of a lexeme has been and remains a current and interesting problem in linguistics. It can encompass the fields of contrastive linguistics, sociolinguistics, and psycholinguistics. This allows us to uncover different variations of the basic meaning and then evaluate them using extralinguistic approaches. The investigation of word meaning must be based on culture-specific historical and psychological experiences applicable to a particular language community, which does not always appear to be a solution to the problem and gives rise to more in-depth research. It has become more relevant to research the historical changes in meaning and terminology in German and Georgian, the observation and elimination of special linguistic expressions, and the use of the collected material to compare ways of naming individual concepts.